Phosphorus Recovery from Waste Activated Sludge: Microwave Treatment and Ozonation with Acid & Alkaline Pre-treatments - SEMERCİ, NESLİHAN (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
This study investigated phosphorus recovery from activated sludge through ozonation and microwave treatment with acid and alkali pre-treatments. Three main groups (pH treatment & ozonation, pH treatment & microwave, pH treatment & ozonation & microwave) were studied for COD and P release. Results of batch experiments have shown that, optimum pH for sludge disintegration and phosphorus release is 10 according to center dot OH radical formation. Also studying at low pH levels gives an advantage due to effect of acidic condition on cell lysis. Besides, according to results of phosphorus fraction experiments in raw sludge, the other advantage of low pH levels is releasing of apatite (bound to calcium) phosphorus. Both ozonation and microwave treatments were effective for sludge disintegration, the highest COD release was observed after microwave treatment of ozonated samples. However, microwave was much more effective than ozonation on phosphorus, significant amount of phosphorus released into the bulk solution in both ozonation and microwave treatments. Despite of COD release, microwave and ozonation & microwave have similar efficiencies on phosphorus release, ozonation might be negligible before microwave due to high production cost. On the other hand, after analyses of struvite samples, pH = 8.5 and 2 days reaction time was determined as the optimum conditions for struvite purity.
Keywords: Phosphorus recovery; Sludge ozonation; Microwave treatment